Deteksi Pengaruh Financial Stabilty, External Pressure, dan Financial Targets terhadap Financial Statement Fraud - Nisa Riski Rahmalia; Elit Eriyanti; Najunda Dewa Yani; Nur Kabib (Jurnal Akuntansi dan Audit Syariah (JAAiS), 2022)
The purpose of this study was to determine the effect of financial stability, external pressure and financial targets on fraudulent financial statements in manufacturing companies. In this study, the population of manufacturing companies listed on the Jakarta Islamic Index 70 (JII 70) for the 2019-2021 period is used. In the sampling process, the technique used is purposive sampling by producing 16 samples of companies. This study uses data analysis in the form of descriptive statistics, classical assumption test, and hypothesis testing. The results showed that partially the financial stability variable had an influence on financial statement fraud. Meanwhile, external pressure variables and financial targets have no effect on financial statement fraud. Simultaneously, the variables of financial stability, external pressure, and financial targets have an effect on fraudulent financial statements.